Investigating Teachers’ Attitudes towards the Incorporation of Global Education within the English as a Foreign Language (EFL) Context “Ticket to English” textbook as a case study - Attou, Youness; TAHARI, Jamal; Seddik, Mahmoud; Benaissa, Mohamed (International Journal of Language and Literary Studies, 2024)
This study examines the investigation of the integration of global education within the Moroccan English as a Foreign Language (EFL) context, focusing on the attitudes and perceptions of EFL teachers toward the inclusion of global issues and values in secondary public school textbooks. Utilizing a quantitative research methodology, the study employs surveys and questionnaires to gather insights from a carefully selected participant pool. The findings reveal a spectrum of perspectives among teachers, with some emphasizing that integrating global values enhances learners’ global awareness and fosters global citizenship. In contrast, others express concerns that such inclusions may aim to assimilate learners into a homogeneous global culture, potentially suppressing local and national identities. Notably, the study underscores the perception that global education is viewed by some as ideologically driven rather than educationally motivated, prompting critical reflections on the underlying principles guiding these integrations and their alignment with broader educational goals. This article contributes valuable insights for curriculum development and pedagogical considerations in the context of global education in Morocco’s EFL classrooms.